2016
DOI: 10.1073/pnas.1524890113
|View full text |Cite
|
Sign up to set email alerts
|

Obeticholic acid, a synthetic bile acid agonist of the farnesoid X receptor, attenuates experimental autoimmune encephalomyelitis

Abstract: Bile acids are ligands for the nuclear hormone receptor, farnesoid X receptor (FXR). The bile acid–FXR interaction regulates bile acid synthesis, transport, and cholesterol metabolism. Recently, bile acid–FXR regulation has been reported to play an integral role in both hepatic and intestinal inflammation, and in atherosclerosis. In this study, we found that FXR knockout mice had more disease severity in experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS). Obeticholic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 57 publications
8
53
0
Order By: Relevance
“…The anti-inflammatory phenotype induced by GW4064-mediated activation of FXR in peripheral myeloid cells, such as BMMs, is well documented [15, 25]. However, expression of FXR is not limited to myeloid cells, but is also present in microglia as well as astrocytes [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-inflammatory phenotype induced by GW4064-mediated activation of FXR in peripheral myeloid cells, such as BMMs, is well documented [15, 25]. However, expression of FXR is not limited to myeloid cells, but is also present in microglia as well as astrocytes [25].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with its expression pattern, FXR activation has been shown to confer protection in several animal models of innate intestinal and hepatic inflammation [11]. In experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS), pharmacological activation of FXR significantly ameliorated the disease course by induction of anti-inflammatory macrophages [15, 25]. Interestingly, FXR agonists are currently tested in clinical trials for treatment of alcoholic hepatitis, type 2 diabetes mellitus and primary biliary cirrhosis, demonstrating that FXR already represents an attractive pharmacological target in human metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study involving the ovalbumin-induced acute murine asthma model, CDCA administration lead to reduced infiltration of cells into the airspace and peribronchial areas, goblet cell hyperplasia, mucus secretion and serum immunoglobulin E levels, as well as reduced T helper type 2 cytokines such as IL-4, IL-5 and IL-13, and TNF-α, suggesting FXR agonists may have therapeutic potential in allergic asthma [45]. In the EAE mouse model, FXR-/-mice exhibited increased disease severity compared to wild type mice, while FXR agonist administration resulted in reduced lymphocyte activation and cytokine production, suggesting FXR agonists may also have therapeutic potential in multiple sclerosis [12].…”
Section: ) Fxrmentioning
confidence: 99%
“…Recently, bile acids were found to regulate inflammation and mediate immune homeostasis [9][10][11][12][13][14][15][16]. Moreover, natural, semi-synthetic, and fully synthetic drugs that target these receptors were developed and are currently being studied for use in various inflammatory disorders such as alcoholic hepatitis, non-alcoholic steatohepatitis, primary biliary cirrhosis, primary sclerosing cholangitis [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The farnesoid X receptor (FXR) is a target for bile acids. Recent extensive study of FXR has shown its ability to down‐regulate inflammation in multiple target organs including the liver, intestine and brain . Activation of FXR reduces bile acid synthesis through inhibition of cholesterol 7‐alpha‐hydroxylase (CYP7A1), known to be the rate limiting step of bile acid synthesis .…”
Section: Currently Approved Treatments For Pbcmentioning
confidence: 99%